ANALISIS BIBLIOMETRIK PENGHINDARAN PAJAK MENGGUNAKAN VOSVIEWER - johar, farhan maulana (Universitas Sangga Buana, 2024)
Tax avoidance is a phenomenon that has become a special concern for the state. Tax avoidance can be understood as a process by which a company tries to reduce income tax payments to tax collecting organizations. The purpose of this study is to identify and analyze research trends in the literature related to tax avoidance and to identify recommendations for future tax avoidance research. The research is qualitative research, the method used in this research is a bibliometric approach. Bibliometric analysis is generally widely used in various disciplines and focuses on quantitative studies on journals or the like. the findings found that there were 10 clusters with 90 items using VOSviewer softaware. The most widely used keyword variables are 'tax avoidance', 'profitability', 'leverage', but for the keywords 'cost of debt', 'cash effective tax rate' there is still little research to be done. Based on the development of publications.